The Development of Culture Book Media to Cultivate Love for the Homeland in Early Childhood - Mahesti, Jeni Anggun; Kusumastuti, Narendradewi; Rachman, Budi (Universitas Pendidikan Indonesia Kampus Serang, 2024)
The purpose of this development research is to create a valid, effective, efficient, and attractive Culture Book Media to foster a sense of love for the homeland in children aged 5-6 years. Instilling a sense of love for the homeland from an early age is one effort to protect children from external threats that enter through culture. Training the generation to be able to foster a sense of love for the homeland is the foundation for the future. This type of research is research and development, which refers to the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The results of this study are based on the results of validation on the aspects of effectiveness, efficiency, and usefulness through trials of subject matter experts, media experts, group trials of 15 children as subjects, and field trials of 32 children aged 5-6 years. The test resulted in an assessment achievement of 95% in the effectiveness aspect, 94.44% in the efficiency aspect, and 95% in the attractiveness aspect. This indicates that the Culture Book Media provides a positive contribution and impact in fostering a sense of love for the homeland. The Culture Book Media is very effective as an alternative learning media and supports teachers in efforts to foster children's love for the homeland.